World Economic System and Islamic Economic System - Widya, Widya; Fahmi, Muhammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of studying economics is to be able to identify connections and solve problems using proven techniques, to understand how decisions are made. This decision-making framework can be used for various regional and global economic issues, to create conducive conditions, all economic actors can collaborate and work harmoniously and exercise creativity in business and independence is of course another goal. This article is a research and reflection on some literature related to the view of the world economic system with the Islamic economic system and its influence on society. Therefore, this article is a literature review by collecting some data from various sources of information some reference articles related to the topic of discussion and furthermore data is also obtained from sources and foundations of Islamic law. The economic system that Hatta wants to build is an economic system whose philosophy and values, both basic and instrumental values, are extracted from the teachings of the Islamic religion. Hatta did not awkwardly mention Islam because Hatta believed that the core values of Islamic teachings would not conflict with other religious values because the values brought by Islamic teachings were universal.